Examining Gaze Cone Shape and Size. (December 2021) - Horstmann, Gernot; Linke, Linda
Another person's looking behavior is used by observers to judge gaze direction and fixation points. An important task in this context is the judgement of direct gaze, that is, the perception of being looked at. The cone of gaze can be defined as the range of fixation points that support direct gaze. The cone concept implies that this range lawfully increases with distance, but that the cone angle is constant. The present experiment tested the concept with a larger number and a more extended range of distances than previously done, and took care of possible directional errors. The gaze cone was found to be roughly linear, and stable between 1.6 m and 7.9 m – an almost perfect cone. The mean cone size subtended 5.2° in diameter when averaged over ascending and descending series. Measures differed, however, in ascending and descending series, consistent with a conservative bias. Also, the variability of judgements increased slightly with distance. Results are discussed considering whether cone size is actually smaller than often reported in the literature.